Physical characteristics of Swedish female professional ice hockey players allowed body checking - Lahti, A.; Grundberg, A.; Stenman, E.; Sundquist, K. (The Journal of Strength and Conditioning Research, 2025)
In ice hockey, physical characteristics impact sporting performance. This study aims to describe body height, body mass, and body mass index (BMI) in professional female ice hockey players in the Swedish Women's Hockey League (SDHL), which is unique as it is (so far) the only women's league in the world that allows body checking. This study also compares physical characteristics by players' position and the players in SDHL with the nonchecking female North American Elite League (PWHL). In addition, attitudes toward body checking are examined. All 225 players registered in SDHL 2023/2024 were invited to participate. Data from 159 included players (71%) aged (mean ± SD) 23.6 ± 4.5 years were analyzed. Body height, body mass, BMI, and attitudes toward body checking were assessed through a self-reported questionnaire. The mean body height was 169.1 ± 5.5 cm, body mass 68.4 ± 6.7 kg, and BMI 23.9 ± 1.9 kg·m-2. No significant differences were found by player position or between the players in SDHL and PWHL. In total, 88% believed that it was good to introduce body checking in women's ice hockey and 64% did not believe that introducing body checking would increase the number of injuries. The observed characteristics may represent baseline reference values of physical characteristics in female ice hockey players allowed body checking. There is currently no difference in physical characteristics by players' positions or between checking and nonchecking leagues although such differences may occur in the future. Most players were positive toward body checking in women's ice hockey and did not believe that the number of injuries would increase by introducing it.